Cardiovascular Disease in Rheumatoid Arthritis: A Systematic Literature Review in Latin America - Sarmiento-Monroy, Juan Camilo (Hindawi Publishing Corporation, 2012)
Background. Cardiovascular disease (CVD) is the major predictor of poor prognosis in rheumatoid arthritis (RA) patients. There is an increasing interest to identify “nontraditional” risk factors for this condition. Latin Americans (LA) are considered as a minority subpopulation and ethnically different due to admixture characteristics. To date, there are no systematic reviews of the literature published in LA and the Caribbean about CVD in RA patients. Methods. The systematic literature review was done by two blinded reviewers who independently assessed studies for eligibility. The search was completed through PubMed, LILACS, SciELO, and Virtual Health Library scientific databases. Results. The search retrieved 10,083 potential studies. A total of 16 articles concerning cardiovascular risk factors and measurement of any cardiovascular outcome in LA were included. The prevalence of CVD in LA patients with RA was 35.3%. Non-traditional risk factors associated to CVD in this population were HLA-DRB1 shared epitope alleles, rheumatoid factor, markers of chronic inflammation, long duration of RA, steroids, familial autoimmunity, and thrombogenic factors. Conclusions. There is limited data about CVD and RA in LA. We propose to evaluate cardiovascular risk factors comprehensively in the Latin RA patient and to generate specific public health policies in order to diminish morbi-mortality rates.